The Analysis of Employee Loyalty at the Muslimat General Hospital in Ponorogo Regency - Hanistin Atslatul Fihani; Near Anggreini Hesti Noviana (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Employee loyalty refers to a person's tendency to remain loyal and committed to the company where they work. Therefore, decent wages are one of the key factors that can influence the level of employee loyalty to the institution where they work. The issue of employee wages is a crucial aspect in human resource management, including in health service institutions such as hospitals. Interestingly, work loyalty still appears even though the amount of wages received is not high. This phenomenon is seen in the Muslimat General Hospital of Ponorogo Regency, where a number of employees show high loyalty to the institution. This study aims to determine the wage conditions and analyze employee loyalty from a wage perspective. The approach used is qualitative with descriptive methods, through in-depth interviews, field observations, and documentation. The results show that employee loyalty is not only influenced by financial factors, but mainly by a conducive work environment, religious values, harmonious interpersonal relationships, and support for self-development. In conclusion, loyalty is formed from a combination of material and non-material aspects, where non-material factors are the dominant elements in maintaining employee loyalty at the Muslimat General Hospital of Ponorogo Regency. This finding emphasizes the importance of managerial strategies that prioritize spiritual and social values ​​in forming employee loyalty in the hospital environment.